Low-absorption high-emission radiation refrigeration coating filler and preparation method thereof

Through technical means such as co-precipitation and yttrium ion doping, radiation refrigeration coating fillers with high reflectivity and emissivity were prepared, which solved the problems of insufficient performance and poor durability in the existing technology, and achieved better radiation refrigeration effect and UV aging resistance.

CN119463566APending Publication Date: 2025-02-18BEIJING SATELLITE MFG FACTORY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411477899.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing radiation refrigeration coating fillers have insufficient performance in terms of solar spectrum reflection capacity and radiation capacity under atmospheric windows, and are prone to discoloration due to long-term irradiation, resulting in a degradation in performance.

Method used

The filler is prepared by co-precipitation method, and by controlling the system uniformity and process parameters of the material precipitation precursor, the uniform distribution of the material phases and wide band high reflectivity are achieved. At the same time, through yttrium ion doping and multi-stage mixing of precursors, the density of the powder and the radiation refrigeration function are improved.

Benefits of technology

The prepared filler has high solar spectral reflectivity and radiance under atmospheric windows, and has good UV aging resistance, and can be used in multiple fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463566A_ABST
    Figure CN119463566A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a low-absorption high-emission radiation refrigeration coating filler, which comprises the following steps: blending a coprecipitation raw material, a doping raw material and a solvent A to obtain a component C; blending a coprecipitator and a solvent B to obtain a component D; dropwise adding the component C into the component D, continuously stirring after dropwise adding, and standing and aging to obtain a component E; filtering, washing and drying the component E to obtain a coprecipitation precursor I; grinding and dispersing the coprecipitation precursor I to obtain a coprecipitation precursor II; and carrying out thermal decomposition treatment and sintering on the coprecipitation precursor II, and naturally cooling to obtain the filler. The invention also discloses the low-absorption high-emission radiation refrigeration coating filler obtained by the method. The obtained filler is uniform in particle size distribution, high in solar spectrum reflecting capacity and high in radiation capacity under an atmospheric window, has good ultraviolet aging resistance and can be applied to multiple fields of high-end optical instrument detection, communication electronics, petrochemical engineering, energy-saving buildings and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of radiation refrigeration materials, and in particular to a low-absorption and high-emission radiation refrigeration coating filler and a preparation method thereof. Background Art

[0002] Radiative cooling is a passive cooling method that does not consume electricity or other energy. Its principle is that the material has a high reflective performance in the solar spectrum, and at the same time converts the remaining absorbed sunlight and the heat emitted by the surrounding higher temperature objects into its own internal energy and then emits it outward in the form of infrared radiation. The heat is dissipated into the outer space with a cold black background through the atmospheric window (8μm~13μm) to achieve the effect of passive cooling. Existing radiative cooling coatings mostly use single particle size powders, which have poor reflective ability to sunlight and cannot form a synergistic radiation mechanism. The radiative cooling effect is insufficient, and it is easy to discolor after long-term exposure, resulting in performance degradation. Summary of the invention

[0003] The purpose of the present invention is to overcome the above defects, provide a low-absorption and high-emission radiation refrigeration coating filler and a preparation method thereof, and solve the technical problems that the existing radiation refrigeration coating filler has poor uniformity, and the performance such as solar spectrum reflection ability and radiation ability under the atmospheric window cannot meet the requirements. The filler obtained by the present invention has uniform particle size distribution, high solar spectrum reflection ability, strong radiation ability under the atmospheric window, and good resistance to ultraviolet aging, and can be applied to multiple fields such as high-end optical instrument detection, communication electronics, petrochemical industry, energy-saving buildings, etc.

[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0005] A method for preparing a low-absorption and high-emission radiation refrigeration coating filler, comprising:

[0006] S1: blending the coprecipitation raw material, the doping raw material and the solvent A to obtain a C component;

[0007] S2: blending the coprecipitant and solvent B to obtain component D;

[0008] S3, under stirring conditions, adding component C dropwise to component D, continuing stirring after the addition is completed, and obtaining component E after standing and aging; filtering, washing, and drying component E to obtain coprecipitation precursor I;

[0009] S4: grinding and dispersing the coprecipitation precursor I, filtering, washing, and drying the obtained product to obtain the coprecipitation precursor II;

[0010] S5 thermally decomposes the coprecipitated precursor II;

[0011] S6 sintering the heat-treated coprecipitated precursor II, and obtaining the filler after natural cooling.

[0012] Furthermore, the molar ratio of the coprecipitation raw material, the doping raw material, the coprecipitation agent, the solvent A and the solvent B is 1:0.05-0.25:2.05-2.35:200-250:10-15.

[0013] Further, the coprecipitation raw material includes one or more of zinc chloride, zinc nitrate, zirconium chloride, hafnium chloride or hafnium nitrate;

[0014] The doping raw material includes one or more of yttrium chloride or yttrium nitrate;

[0015] The coprecipitant includes one or more of ammonia or urea;

[0016] The solvent A includes one or more of methanol, ethanol or n-butanol, and the solvent B is the same as the solvent A.

[0017] Further, in step S3, the stirring speed is 800-1000 rpm, and the dripping speed of component C is 5-10 ml / min;

[0018] After the dropwise addition is completed, stirring is continued for 2 to 4 hours, and the mixture is allowed to stand and age for 12 to 20 hours to obtain component E.

[0019] Furthermore, in step S4, the grinding medium used for grinding and dispersion is spherical zirconium oxide, the purity of zirconium oxide is ≥99.9%, the particle size of zirconium oxide is 2 mm to 8 mm, and the filling volume of zirconium oxide is 75% to 85%;

[0020] The grinding process uses water cooling to control the temperature of the grinding jar below 30°C, and the grinding and dispersion time is 8 to 12 hours.

[0021] Furthermore, in step S3 and step S4, a sand core funnel is used for filtering, and the mixture is dried by baking at 95 to 105° C. for 24 to 36 hours.

[0022] Furthermore, in step S5, the thermal decomposition temperature is 450°C to 650°C, and the heating time is 3 to 5 hours.

[0023] Furthermore, in step S6, the sintering temperature is 950° C. to 1050° C., and the sintering time is 2 to 4 hours.

[0024] A low-absorption and high-emission radiation refrigeration coating filler is obtained by adopting the above-mentioned preparation method of the low-absorption and high-emission radiation refrigeration coating filler.

[0025] Furthermore, the particle size of the filler is 0.5-2.5 μm; the reflectivity of 200 nm-2500 nm is 0.90-0.93; the emissivity of 8 μm-13 μm is 0.90-0.92; after 1000 UV aging, the reflectivity changes by ≤0.01, and the emissivity changes by ≤0.01.

[0026] Compared with the prior art, the present invention has at least one of the following beneficial effects:

[0027] (1) The present invention adopts a coprecipitation method to effectively control the system uniformity of the material precipitation precursor, which ensures the uniform distribution of the material phase to a certain extent. At the same time, by controlling the coprecipitation process parameters and the solid phase sintering parameters, the particle size of the powder is matched with the spectral energy to achieve high reflectivity in a wide band;

[0028] (2) The present invention can effectively control the powder particle size, improve the powder density, and reduce the stoichiometric ratio defects through multi-stage mixing of precursors. The prepared powder has excellent radiation cooling function;

[0029] (3) The present invention can effectively enhance the lattice vibration of filler powder by doping with yttrium ions, thereby achieving high radiation characteristics in the infrared band. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a test chart of the particle size distribution of the filler powder prepared by the present invention;

[0031] Figure 2 (a) is an electron microscope photograph of a powder prepared by a conventional method of the present invention, and (b) is an electron microscope photograph of a powder prepared by the method of the present invention. DETAILED DESCRIPTION

[0032] The following detailed description of the present invention will make the features and advantages of the present invention more clear and explicit.

[0033] The word "exemplary" is used exclusively herein to mean "serving as an example, embodiment, or illustration." Any embodiment described herein as "exemplary" is not necessarily to be construed as preferred or advantageous over other embodiments. Although various aspects of the embodiments are shown in the drawings, the drawings are not necessarily drawn to scale unless otherwise noted.

[0034] The present invention provides a modified preparation method for oxide powder doped with yttrium ions to improve the lattice vibration of filler powder and thus achieve high radiation characteristics in the infrared band. The powder particle size can be effectively controlled, the powder density can be improved, and the stoichiometric ratio defects can be reduced through multi-stage mixing of precursors. The prepared powder has excellent radiation refrigeration function.

[0035] The radiation cooling filler powder of the present invention has excellent radiation cooling function and anti-ultraviolet aging performance. The present invention adopts coprecipitation technology to effectively control the system uniformity of the material precipitation precursor, and to a certain extent ensures the uniform distribution of the material phase. At the same time, by controlling the coprecipitation process parameters and the solid phase sintering parameters, the particle size of the powder is matched with the spectral energy to achieve high reflection performance in a wide band; the multi-stage dispersion of the precursor is adopted to improve the mixing uniformity between the phases, and reduce the stoichiometric ratio defects and component segregation.

[0036] The invention discloses a modified preparation method for a low-absorption and high-emission radiation refrigeration coating filler, which mainly comprises three parts: coprecipitation, multi-stage dispersion and high-temperature sintering.

[0037] (1) The coprecipitation process comprises the following steps:

[0038] 1) Weigh a coprecipitation raw material, a doping raw material, a coprecipitant, a solvent A and a solvent B in a molar ratio of 1:0.05-0.25:2.05-2.35:200-250:10-15, wherein the coprecipitation raw material comprises one of zinc chloride, zinc nitrate, zirconium chloride, hafnium chloride and hafnium nitrate, the doping raw material comprises one of yttrium chloride and yttrium nitrate, the coprecipitant comprises one of ammonia water and urea, the solvent A comprises one of methanol, ethanol and n-butanol, and the solvent B is consistent with the solvent A.

[0039] 2) The coprecipitation raw material, the doping raw material and the solvent A are blended, and the mixture is stirred in a closed state with a high-speed stirrer for 2 to 4 hours at a stirring rate of 350 rpm to 550 rpm to obtain the C component; the coprecipitant and the solvent B are blended, and the mixture is stirred in a closed state with a high-speed stirrer for 2 to 4 hours at a stirring rate of 350 rpm to 550 rpm to obtain the D component.

[0040] 3) The stirring speed of component C is adjusted to 800-1000 rpm, and component D is slowly added at a speed of 5-10 ml / min. After all component D is added, stirring is continued for 2-4 hours, and then allowed to stand for 12-20 hours to obtain component E;

[0041] 4) The precipitate in component E is filtered and washed using a sand core funnel, and baked at 95-105° C. for 24-36 hours to obtain a dry coprecipitation precursor, which is a basic metal precipitate containing rare earth ions.

[0042] (2) The precursor multi-stage dispersion process includes the following steps:

[0043] 1) Grinding and dispersing the coprecipitated precursor obtained in step (1), using spherical zirconium oxide as the grinding medium, with a zirconium oxide purity of ≥99.9%, a zirconium oxide particle size of 2 mm to 8 mm, and a zirconium oxide filling volume of 75% to 85%. The grinding process is water-cooled, the temperature of the grinding jar is controlled to be below 30° C., and the grinding and dispersing time is 8 to 12 hours;

[0044] 2) After grinding and dispersion, filter and wash with a sand core funnel, and bake at 95-105° C. for 24-36 hours to obtain a dry multi-stage dispersed coprecipitation precursor;

[0045] (3) The high temperature sintering process includes the following steps:

[0046] 1) thermally decomposing the dried multi-stage dispersed coprecipitation precursor obtained in step (2) at a high temperature of 450° C. to 650° C. for 3 to 5 hours; in this step, the difference in reaction temperature and time has an effect on the filler particle size, which ultimately results in a difference in the thermal radiation performance of the filler;

[0047] 2) The powder after thermal decomposition is subjected to high temperature sintering at a temperature of 950° C. to 1050° C. for a sintering time of 2 to 4 hours, and then naturally cooled to obtain the low-absorption and high-emission radiation refrigeration coating filler of the present invention.

[0048] The low-absorption and high-emission radiation refrigeration coating filler provided by the present invention has the following characteristics:

[0049] 1) Appearance: The powder is white and evenly distributed;

[0050] 2) Particle size: 0.5-2.5 μm;

[0051] 3) Reflectivity of 200nm~2500nm: 0.90~0.93;

[0052] 4) Emissivity of 8μm to 13μm: 0.90 to 0.92;

[0053] 5) UV aging resistance: After 1000 UV aging, the reflectivity change is ≤0.01, and the emissivity change is ≤0.01;

[0054] like Figure 1 and Figure 2 Compared with the existing powder materials of the same type, the low-absorption and high-emission radiation refrigeration coating filler powder of the present invention has a more uniform particle size distribution, significantly improved solar spectrum reflection ability, significantly improved radiation ability under the atmospheric window, and good resistance to ultraviolet aging. It can be used in high-end optical instrument detection, communication electronics, petrochemical industry, energy-saving buildings and other fields.

[0055] Example:

[0056] Example 1

[0057] 1) Weigh a coprecipitation raw material, a doping raw material, a coprecipitant, a solvent A and a solvent B in a molar ratio of 1:0.05:2.05:200:10, wherein the coprecipitation raw material is zinc chloride, the doping raw material is yttrium chloride, the coprecipitant is ammonia water, the solvent A is methanol, and the solvent B is consistent with the solvent A.

[0058] 2) The coprecipitation raw material, the doping raw material and the solvent A are blended, and the mixture is stirred in a closed state with a high-speed stirrer for 2 hours at a stirring rate of 350 rpm to obtain the C component; the coprecipitant and the solvent B are blended, and the mixture is stirred in a closed state with a high-speed stirrer for 2 hours at a stirring rate of 350 rpm to obtain the D component.

[0059] 3) The stirring speed of component C was adjusted to 800 rpm, and component D was slowly added at a speed of 5 ml / min. After all component D was added, stirring was continued for 2 hours, and then allowed to stand for 12 hours to obtain component E;

[0060] 4) The precipitate in component E was filtered and washed using a sand core funnel, and baked at 95° C. for 36 h to obtain a dry coprecipitation precursor.

[0061] 5) Grinding and dispersing the coprecipitated dry powder, using spherical zirconium oxide as the grinding medium, with a zirconium oxide purity of ≥99.9%, a zirconium oxide particle size of 2 mm, and a zirconium oxide filling volume of 75%. The grinding process uses water cooling to dissipate heat, and the temperature of the grinding jar is controlled below 30° C. The grinding and dispersing time is 8 hours;

[0062] 6) After grinding and dispersion, filter and wash with a sand core funnel, and bake at 95° C. for 36 hours to obtain a dry multi-stage dispersed coprecipitation precursor;

[0063] 7) thermally decomposing the obtained dried multi-stage dispersed co-precipitation precursor at high temperature, the temperature is 450° C., and the heating time is 3 h;

[0064] 8) The powder after thermal decomposition is subjected to high temperature sintering at a temperature of 950° C. for 2 hours, and then naturally cooled to obtain the low-absorption and high-emission radiation refrigeration coating filler of the present invention.

[0065] The low-absorption and high-emission radiation refrigeration coating filler provided by the present invention has the following characteristics:

[0066] 1) Appearance: The powder is white and evenly distributed;

[0067] 2) Particle size: 0.5-1.5 μm;

[0068] 3) Reflectivity of 200nm~2500nm: 0.93;

[0069] 4) Emissivity of 8μm to 13μm: 0.90;

[0070] 5) UV aging resistance: After 1000 UV aging, the reflectivity change is ≤0.01, and the emissivity change is ≤0.01.

[0071] Example 2

[0072] 1) Weigh a coprecipitation raw material, a doping raw material, a coprecipitant, a solvent A and a solvent B in a molar ratio of 1:0.25:2.35:250:15, wherein the coprecipitation raw material is zirconium chloride, the doping raw material is yttrium nitrate, the coprecipitant is urea, the solvent A is ethanol, and the solvent B is consistent with the solvent A.

[0073] 2) The coprecipitation raw material, the doping raw material and the solvent A are blended, and the mixture is stirred in a closed state with a high-speed stirrer for 4 hours at a stirring rate of 550 rpm to obtain the C component; the coprecipitant and the solvent B are blended, and the mixture is stirred in a closed state with a high-speed stirrer for 4 hours at a stirring rate of 550 rpm to obtain the D component.

[0074] 3) The stirring speed of component C was adjusted to 1000 rpm, and component D was slowly added at a speed of 10 ml / min. After all component D was added, stirring was continued for 4 hours, and then allowed to stand and age for 20 hours to obtain component E;

[0075] 4) The precipitate in component E was filtered and washed using a sand core funnel, and baked at 105° C. for 24 h to obtain a dry coprecipitation precursor.

[0076] 5) Grinding and dispersing the obtained coprecipitated dry powder, using spherical zirconium oxide as the grinding medium, with a zirconium oxide purity of ≥99.9%, a zirconium oxide particle size of 8 mm, and a zirconium oxide filling volume of 85%. The grinding process uses water cooling to dissipate heat, and the temperature of the grinding jar is controlled below 30° C. The grinding and dispersing time is 12 hours;

[0077] 6) After grinding and dispersion, filter and wash with a sand core funnel, and bake at 105° C. for 24 hours to obtain a dry multi-stage dispersed coprecipitation precursor;

[0078] 7) thermally decomposing the obtained dried multi-stage dispersed co-precipitation precursor at high temperature, the temperature is 650° C., and the heating time is 3 h;

[0079] 8) The powder after thermal decomposition is subjected to high temperature sintering at a temperature of 1050° C. for 4 hours, and then naturally cooled to obtain the low-absorption and high-emission radiation refrigeration coating filler of the present invention.

[0080] The low-absorption and high-emission radiation refrigeration coating filler provided by the present invention has the following characteristics:

[0081] 1) Appearance: The powder is white and evenly distributed;

[0082] 2) Particle size: 1.5-2.5 μm;

[0083] 3) Reflectivity of 200nm~2500nm: 0.90;

[0084] 4) Emissivity of 8μm to 13μm: 0.92;

[0085] 5) UV aging resistance: After 1000 UV aging, the reflectivity change is ≤0.01, and the emissivity change is ≤0.01.

[0086] Example 3

[0087] 1) Weigh a coprecipitation raw material, a doping raw material, a coprecipitant, a solvent A and a solvent B in a molar ratio of 1:0.15:2.15:220:12, wherein the coprecipitation raw material is hafnium nitrate, the doping raw material is yttrium nitrate, the coprecipitant is ammonia water, the solvent A is n-butanol, and the solvent B is consistent with the solvent A.

[0088] 2) The coprecipitation raw material, the doping raw material and the solvent A are blended, and the mixture is stirred in a closed state with a high-speed stirrer for 3 hours at a stirring rate of 450 rpm to obtain the C component; the coprecipitant and the solvent B are blended, and the mixture is stirred in a closed state with a high-speed stirrer for 3 hours at a stirring rate of 450 rpm to obtain the D component.

[0089] 3) The stirring speed of component C was adjusted to 900 rpm, and component D was slowly added at a speed of 5 ml / min. After all component D was added, stirring was continued for 3 hours, and then allowed to stand for 16 hours to obtain component E;

[0090] 4) The precipitate in component E was filtered and washed using a sand core funnel, and baked at 100° C. for 30 h to obtain a dry coprecipitation precursor.

[0091] 5) Grinding and dispersing the obtained coprecipitated dry powder, using spherical zirconium oxide as the grinding medium, with a zirconium oxide purity of ≥99.9%, a zirconium oxide particle size of 4 mm, and a zirconium oxide filling volume of 80%. The grinding process uses water cooling to dissipate heat, and the temperature of the grinding jar is controlled below 30° C. The grinding and dispersing time is 10 hours;

[0092] 6) After grinding and dispersion, filter and wash with a sand core funnel, and bake at 100° C. for 30 hours to obtain a dry multi-stage dispersed coprecipitation precursor;

[0093] 7) thermally decomposing the obtained dried multi-stage dispersed co-precipitation precursor at high temperature, the temperature is 550° C., and the heating time is 4 h;

[0094] 8) The powder after thermal decomposition is subjected to high temperature sintering at a temperature of 1000° C. for 3 hours, and then naturally cooled to obtain the low-absorption and high-emission radiation refrigeration coating filler of the present invention.

[0095] The low-absorption and high-emission radiation refrigeration coating filler provided by the present invention has the following characteristics:

[0096] 1) Appearance: The powder is white and evenly distributed;

[0097] 2) Particle size: 1.0-2.0 μm;

[0098] 3) Reflectivity of 200nm~2500nm: 0.92;

[0099] 4) Emissivity of 8μm to 13μm: 0.91;

[0100] 5) UV aging resistance: After 1000 UV aging, the reflectivity change is ≤0.01, and the emissivity change is ≤0.01.

[0101] Comparative Example 1

[0102] The difference between this comparative example and Example 3 is that no doping raw material is added, and the specific steps are as follows:

[0103] 1) Weigh a coprecipitation raw material, a coprecipitant, a solvent A and a solvent B in a molar ratio of 1:2.15:220:12, wherein the coprecipitation raw material is hafnium nitrate, the coprecipitant is ammonia water, the solvent A is n-butanol, and the solvent B is consistent with the solvent A.

[0104] 2) The coprecipitation raw material and solvent A are blended, and stirred in a closed state with a high-speed stirrer for 3 hours at a stirring rate of 450 rpm to obtain component C; the coprecipitant and solvent B are blended, and stirred in a closed state with a high-speed stirrer for 3 hours at a stirring rate of 450 rpm to obtain component D.

[0105] 3) The stirring speed of component C was adjusted to 900 rpm, and component D was slowly added at a speed of 5 ml / min. After all component D was added, stirring was continued for 3 hours, and then allowed to stand for 16 hours to obtain component E;

[0106] 4) The precipitate in component E was filtered and washed using a sand core funnel, and baked at 100° C. for 30 h to obtain a dry coprecipitation precursor.

[0107] 5) Grinding and dispersing the obtained coprecipitated dry powder, using spherical zirconium oxide as the grinding medium, with a zirconium oxide purity of ≥99.9%, a zirconium oxide particle size of 4 mm, and a zirconium oxide filling volume of 80%. The grinding process uses water cooling to dissipate heat, and the temperature of the grinding jar is controlled below 30° C. The grinding and dispersing time is 10 hours;

[0108] 6) After grinding and dispersion, filter and wash with a sand core funnel, and bake at 100° C. for 30 hours to obtain a dry multi-stage dispersed coprecipitation precursor;

[0109] 7) thermally decomposing the dried multi-stage dispersed coprecipitation precursor obtained in step 2 at high temperature, the temperature is 550° C., and the heating time is 4 h;

[0110] 8) The powder after thermal decomposition was sintered at a high temperature of 1000° C. for 3 h, and then naturally cooled to obtain the comparative example filler of the present invention.

[0111] The comparative filler of the present invention has the following characteristics:

[0112] 1) Appearance: The powder is white and evenly distributed;

[0113] 2) Particle size: 1.0-2.0 μm;

[0114] 3) Reflectivity of 200nm~2500nm: 0.90;

[0115] 4) Emissivity of 8μm to 13μm: 0.85;

[0116] 5) UV aging resistance: After 1000 UV aging, the reflectivity change is ≤0.03, and the emissivity change is ≤0.02.

[0117] By comparing Example 3 with Comparative Example 1, it can be seen that the present invention can effectively improve the radiation characteristics in the infrared band by doping with yttrium.

[0118] The present invention has been described in detail above in conjunction with specific implementations and exemplary examples, but these descriptions cannot be understood as limiting the present invention. Those skilled in the art understand that, without departing from the spirit and scope of the present invention, a variety of equivalent substitutions, modifications or improvements may be made to the technical solution of the present invention and its implementation methods, all of which fall within the scope of the present invention. The scope of protection of the present invention shall be subject to the attached claims.

[0119] The contents not described in detail in the specification of the present invention belong to the common knowledge of those skilled in the art.

Claims

1. A method for preparing a low-absorption and high-emission radiation refrigeration coating filler, characterized in that: include: S1: blending the coprecipitation raw material, the doping raw material and the solvent A to obtain a C component; S2: blending the coprecipitant and solvent B to obtain component D; S3, under stirring conditions, adding component C dropwise to component D, continuing stirring after the addition is completed, and obtaining component E after standing and aging; filtering, washing, and drying component E to obtain coprecipitation precursor I; S4: grinding and dispersing the coprecipitation precursor I, filtering, washing, and drying the obtained product to obtain the coprecipitation precursor II; S5 thermally decomposes the coprecipitated precursor II; S6 sintering the heat-treated coprecipitated precursor II, and obtaining the filler after natural cooling.

2. The method for preparing a low-absorption and high-emission radiation refrigeration coating filler according to claim 1, characterized in that: The molar ratio of the coprecipitation raw material, the doping raw material, the coprecipitation agent, the solvent A and the solvent B is 1:0.05-0.25:2.05-2.35:200-250:10-15.

3. The method for preparing a low-absorption and high-emission radiation refrigeration coating filler according to claim 1, characterized in that: The coprecipitation raw materials include one or more of zinc chloride, zinc nitrate, zirconium chloride, hafnium chloride or hafnium nitrate; The doping raw material includes one or more of yttrium chloride or yttrium nitrate; The coprecipitant includes one or more of ammonia or urea; The solvent A includes one or more of methanol, ethanol or n-butanol, and the solvent B is the same as the solvent A.

4. The method for preparing a low-absorption and high-emission radiation refrigeration coating filler according to claim 1, characterized in that: In step S3, the stirring speed is 800-1000 rpm, and the dropping speed of component C is 5-10 ml / min; After the dropwise addition is completed, stirring is continued for 2 to 4 hours, and the mixture is allowed to stand for 12 to 20 hours to obtain component E.

5. The method for preparing a low-absorption and high-emission radiation refrigeration coating filler according to claim 1, characterized in that: In step S4, the grinding medium used for grinding and dispersion is spherical zirconium oxide, the purity of zirconium oxide is ≥99.9%, the particle size of zirconium oxide is 2 mm to 8 mm, and the filling volume of zirconium oxide is 75% to 85%; The grinding process uses water cooling to control the temperature of the grinding jar below 30°C, and the grinding and dispersion time is 8 to 12 hours.

6. The method for preparing a low-absorption and high-emission radiation refrigeration coating filler according to claim 1, characterized in that: In step S3 and step S4, a sand core funnel is used for filtering, and the product is dried by baking at 95 to 105° C. for 24 to 36 hours.

7. The method for preparing a low-absorption and high-emission radiation refrigeration coating filler according to claim 1, characterized in that: In step S5, the thermal decomposition temperature is 450°C to 650°C, and the heating time is 3 to 5 hours.

8. The method for preparing a low-absorption and high-emission radiation refrigeration coating filler according to claim 1, characterized in that: In step S6, the sintering temperature is 950° C. to 1050° C., and the sintering time is 2 to 4 hours.

9. A low-absorption and high-emission radiation refrigeration coating filler, characterized in that: The low-absorption and high-emission radiation refrigeration coating filler is obtained by the preparation method of any one of claims 1 to 8.

10. The low-absorption and high-emission radiation refrigeration coating filler according to claim 9, characterized in that: The particle size of the filler is 0.5-2.5 μm; the reflectivity of 200 nm-2500 nm is 0.90-0.93; the emissivity of 8 μm-13 μm is 0.90-0.92; after 1000 UV aging, the reflectivity changes by ≤0.01, and the emissivity changes by ≤0.01.

Citation Information

Patent Citations

  • Small-particle-size cerium-doped yttrium aluminum garnet fluorescent powder prepared by coprecipitation method and method and application

    CN107163942A

  • Preparation method of rare earth doped YSZ phosphorescent powder

    CN115287064A

  • Low-temperature co-precipitation method for fabricating TCO powders

    US20130181175A1

  • Zirconium oxide composite ceramic and preparation method therefor

    US20180134624A1